The Continuing 'Wind of Change' in the Balkans: Sources of Housing Inequality in Bulgaria - Vesselinov, Elena (Urban Studies (Routledge), 2004)
The research in this paper explores the institutional changes in the housing system during the period of market transition in Bulgaria, which follow suit with the greater societal transformations. The societal changes are linked theoretically with Polanyi's understanding of the transition from a non-market to a market society. His argument helps in establishing the institutional context of the macroeconomic changes in the past decade. The article then focuses on the changing sources of housing inequality. It is argued that there are two urban regimes of housing inequality: the regime of controlled uniformity during the period of socialism and the regime of primitive diversity during the period of market transition. The two regimes are produced mainly through the changing role of the state.
Keywords: Bulgaria; cities & towns; equality; housing; macroeconomics; socialism; urban studies

Globalization, Labor and the 'Polanyi Problem' - Munck, Ronaldo (Labor History, 2004)
This article outlines what the Polanyi problem consists of and provides information on some of the implications that arise in developing a Gramscian/Polanyian strategy of counter-hegemony for the labor and the modern social movements, as of August 2004. Labor and new social movements are allegedly an integral element for a progressive solution of the so-called Polanyi problem, which is how the tendency towards the creation of a global free-market economy can be reconciled with a degree of stability and cohesion in society. Taking a Polanyian perspective allows the development of a historical perspective on the dual transformations of globalization and labor. Towards the end of the Second World War, Karl Polanyi wrote of how a self-regulating market that allegedly could not exist for any length of time without annihilating the human and natural substance of society. Such a utopia would allegedly destroy humanity and transform the world into a wilderness, an opinion mirrored by modern eco-socialists. The strategy and ideology of globalization as transformative revolution seems to echo and confirm Polanyi's account of the 19th century industrial revolution, an attempt to set up a self-regulating market.
Keywords: GRAMSCI, Antonio, 1891-1937; Polanyi and Gramsci; Polanyi problem; counter-hegemony; economic policy; free enterprise; globalization; international relations; labor movement; labour movement; social movements

Economic Sociology’s Legacy to Corporate Governance, 2004 - Kahn, Faith Stevelman (Conference Papers -- Law & Society, 2004)
This paper explores the intellectual tradition of Max Weber,Emil Durkheim, Joseph Shumpeter and Karl Polanyi — economic sociologists whose work has been largely ignored by corporate governance scholars focused on the more traditional areas of economics. The foundation laid by Weber is the central focus of the paper. Weber's writing in Economy and Society laid the groundwork for an approach to the study of firms and markets that diverges significantly from that in of the neoclassical economic model. Weber viewed firms and markets as being deeply embedded in and inseparable from the larger systems of social values and social structures that make a society durable. He grounded his view of economic action in a view of social action. Social actions are all deliberate (meaning purposive, which would include deliberately passive) acts undertaken in contemplation of others' acts and reactions. Transactions in money are generally social actions, since the value of money is determined by what people will decide to give you for it! Economic actions are constantly ormed by patterns of meaning, systems of power and social systems (the family....) that underlie them. From this perspective, the growth of the firm has as much to do with the need for rationalization and the rational/economic division of labor (esp. in a condition of limited liability) as it does with any immediate reduction of transaction costs. Rationality ( the struggle for meaning and systems that order chaos) is as pressing a force as efficiency. Recent writing in economics has come close to building a bridge back to economic sociology, especially with its interest in the effects (or lack of) trust in economic transacting as well as other "behavioral" variations. Economic sociology pursues these departures from qualitative rationality at the level of social structure, rather than individual psychological aberrancy. This paper tries to broader this more "socially" oriented view of the behavior of human beings in firms and markets. This intellectual background is related to contemporary issues in corporate governance legislation, and especially the Sarbanes Oxley reforms and then the increased demand for independent directors at public companies and mutual funds.
Keywords: DURKHEIM, Emile; WEBER, Max, 1864-1920; corporate governance; economic sociology; social action; social structure; socioeconomics

The third way and the third world: poverty reduction and social inclusion in the rise of 'inclusive' liberalism - Porter, Doug; Craig, David (Review of International Political Economy, 2004)
In the wake of frank neo-liberalism, and in the context of rising security fears, ways are being found to provide market liberalism with a more inclusive face. The Poverty Reduction Strategies currently prominent in international development, and Thirdway OECD 'Social Inclusion' policy frames claim common purpose to promote 'opportunity, empowerment and security' for people and places on the peripheries of global economies and societies. They share commitments to global economic integration and openness, market led growth, 'good' and 'joined up' governance, local and social partnerships, and wide-ranging activation of 'capacities'. But the high rhetorical aspirations of liberalism to social 'inclusivity' have so far overreached empirical gains for the poor. Drawing on developing country examples of Poverty Reduction Strategy and public policy in New Zealand's current Labour government, this paper sketches salient features of 'inclusive' liberalism. It critically examines its status as a Polanyian turn within a wider liberal project, which seeks to re-embed and legitimate a liberal social and economic order.
Keywords: New Zealand; developing countries; international competition; international political economy; liberalism; political planning; poverty; poverty reduction; self-efficacy; social inclusion; third way

Third Worldism and the lineages of global fascism: the regrouping of the global South in the neoliberal era - Patel, Rajeev; McMichael, Philip (Third World Quarterly, 2004)
We come to an analysis of Third Worldism through an historical understanding of the development project, one that locates Third Worldism as a moment in a broader series of resistances both to capital and colonialism, and to the techniques used by the state to maintain hegemony. Viewing Third Worldism in this wider context, we argue, enables us to not only explain the failure of Third Worldism to deliver on its vision of emancipation from colonialism, but to also explain the shape of contemporary resistance to the world capitalist order. We argue that the theory and practice of development depends on a certain biopolitics, rooted in a regime of sovereign state control, and designed to mobilise citizens in ways favourable to capital. We hold that Third Worldism embraced this form of sovereignty and its biopolitics. Further, by blending cultural studies analysis with a Polanyian interpretation of the rise of fascism, we argue that Third Worldism can be situated as a moment in the maturation of 'global fascism'. Finally, we argue that contemporary resistances to neoliberalism have recognised the complicity of the state with capital. These 'new internationalisms' arise from the ashes of Third Worldism, with an altered understanding of 'sovereignty' that challenges the trajectory of the Third World sovereign state.
Keywords: biopolitics (sociobiology); capitalism; colonies; fascism; global capital; global fascism; hegemony; liberty; sovereignty (political science)

Social Exclusion in a Comparative Context - Reimer, Bill (Sociologia Ruralis, 2004)
This paper outlines a framework for understanding social exclusion that is multidimensional, dynamic, multi-leveled, and relational. Inspired by Polanyi's classification of the modes of economic inclusion, we propose that social inclusion and exclusion processes are rooted in four types of social relations: market (exchange and barter), bureaucratic (rational-legal), associative (common interest), and communal (complex reciprocity and shared identity). Each type reflects different, but integrated processes of social exclusion and inclusion. These four types are outlined conceptually, then operationalized using data from a Canadian survey conducted in 1995 rural households. The results show the extent to which the four types of relations are used for social support, their interdependence, and their relationship to selected household characteristics and outcomes. The policy implications discussed emphasize the ways in which building capacity in all four types of relations can increase the level of social inclusion.
Keywords: Canada; economic inclusion; rural sociology; social exclusion

Desolation and Enlightenment: Political Knowledge After Total War, Totalitarianism, and the Holocaust - Katznelson, Ira (Columbia University Press, 2004)
During and especially after the Second World War, a group of leading scholars who had been perilously close to the war's devastation joined others fortunate enough to have been protected by distance in an effort to redefine and reinvigorate Western liberal ideals for a radically new age. Treating evil as an analytical category, they sought to discover the sources of twentieth-century horror and the potentialities of the modern state in the wake of western desolation. In the process, they devised strikingly new ways to understand politics, sociology and history that reverberate still. In this major intellectual history, Ira Katznelson examines the works of Hannah Arendt, Robert Dahl, Richard Hofstadter, Harold Lasswell, Charles Lindblom, Karl Polanyi, and David Truman, detailing their engagement with the larger project of reclaiming the West's moral bearing. In light of their epoch's calamities these intellectuals insisted that the tradition of Enlightenment thought required a new realism, a good deal of renovation, and much recommitment. This array of historians, political philosophers, and social scientists understood that a simple reassertion of liberal modernism had been made radically insufficient by the enormities and moral catastrophes of war, totalitarianism, and holocaust. Confronting their period's dashed hopes for reason and knowledge, they asked not just whether the Enlightenment should define modernity, but which Enlightenment we should wish to have. Decades later, in the midst of a new type of war and reanimated discussions of the concept of evil, we share no small stake in assessing their successes and limitations.
Keywords: ARENDT, Hannah; World War II; fascism; military history; political history; political philosophy; political theory; totalitarianism

Polanyi Symposium: a conversation on embeddedness - Krippner, Greta; Granovetter, Mark; Block, Fred; Biggart, Nicole; Beamish, Tom; Hsing, Youtien; Hart, Gillian; Arrighi, Giovanni; Mendell, Margie; Hall, John; Burawoy, Michael; Vogel, Steve; et al. (Socio-Economic Review (2004), 2004)
This conversation, transcribed from a conference in April 2002, is intended to illuminate current debates about the use and abuse of the embeddedness concept in economic sociology.
Keywords: economic sociology; embeddedness; markets; symposium

Karl Polanyi o la humildad de las ciencias sociales - Rendueles, César (NEXO. Revista de Filosofía, 2004)
EN: This essay proposes a periodization of Karl Polanyi’s work, from his early writings in Vienna to his anthropological work developed in the context of the substantivist-formalist discussion. The outstanding feature of this studies is the way they combine empirical sharpness with epistemological modesty. Unlike orthodox economy and imperialism theories, Polanyi doesn’t ignore the precarious theoretical situation of social science. His investigations are based on empirical thesis both broadly accepted and heuristically productive. Este artículo analiza las distintas fases de la obra de Karl Polanyi, desde sus pri- meros escritos en Viena a su obra antropológica en el contexto del debate entre sus- tativistas y formalistas. La principal virtud de estos estudios es su mezcla de acier- to empírico y modestia epistemológica. A diferencia de la economía ortodoxa o de las teorías del imperialismo, Polanyi no rehuye la precaria situación teórica de las ciencias sociales. Sus investigaciones se basan en tesis empíricas ampliamente aceptadas que, sin embargo, demuestran una notable vitalidad heurística.
Keywords: Karl Polanyi; epistemology; periodization; social science